Teacher Competence, Innovation, and Commitment in Improving the Quality of Language Learning in the Independent Curriculum Era - Alwi, Muhammad; Safitri, Nursan (Newinera Publisher, 2025)
This study aims to analyze the influence of teacher competence, innovation, and commitment on the quality of language learning in the Merdeka Curriculum era. The background of the study departs from the need to improve teacher quality in facing changes in the learning paradigm that emphasizes creativity, collaboration, and student independence. The research method used is a quantitative approach with a survey of 100 language teachers at the secondary school level. Data analysis was carried out using multiple linear regression with the help of SPSS version 26. The results showed that teacher competence had a significant effect on the quality of learning (t = 2.278; Sig. = 0.026), learning innovation was the most dominant factor (t = 4.126; Sig. = 0.000), and teacher commitment also had a significant positive effect (t = 2.531; Sig. = 0.013). Simultaneously, these three variables had a significant effect on the quality of learning (F = 38.957; Sig. = 0.000) with R² = 0.872. These findings confirm that competent, innovative, and highly committed teachers have a strategic role in increasing the effectiveness and relevance of language learning in schools.